A Method to Hide Text in Image - Al-Saedi, Ahmed Kadem Hamed (جامعة ميسان - كلية التربية, 2016)
The needs for steganography techniques for hiding secret message inside images have been arise. Thus this paper is to create a practical steganography implementation to hide text inside image. It enables the user to provide the system with both text and cover, and obtain a resulting image that contains the hidden text inside. The proposed method consists of two major parts, the first, is procedure to hide a text into a digital image, and the second, is procedure to get a hide text from it. We use the Least Significant Bit method to hide the message or text, in order to keep the features and characteristics of the original image. By experiment and implement of this method by MATLAB® language, the method seems work in a better case by hiding and getting text from a digital image which is used as a carrier of this text.
Keywords: العلامات المائية الرقمية -- إخفاء المعلومات -- الرسائل المخفية